Consumption of Yerba Mate (Ilex paraguariensis) Improves Serum Lipid Parameters in Healthy Dyslipidemic Subjects and Provides an Additional LDL-Cholesterol Reduction in Individuals on Statin Therapy - de Morais, Elayne C; Stefanuto, Aliny; Klein, Graziela A; Boaventura, Brunna C. B; de Andrade, Fernanda; Wazlawik, Elisabeth; Di Pietro, Patrícia F; Maraschin, Marcelo; da Silva, Edson L (Journal of agricultural and food chemistry, 2009)
The objective of this study was to verify the effect of yerba mate (Ilex paraguariensis) consumption on lipid and lipoprotein levels in humans. One hundred and two individuals participated of this single-blind controlled trial. Normolipidemic (n = 15), dyslipidemic (n = 57), and hypercholesterolemic subjects on long-term statin therapy (n = 30) ingested 330 mL, 3 times/day, of green or roasted yerba mate infusions for 40 days. In normolipidemic subjects, yerba mate consumption reduced LDL-cholesterol by 8.7% (p < 0.05). Compared with the baseline period, yerba mate intake by dyslipidemic individuals for 20 and 40 days lowered LDL-cholesterol by 8.1 and 8.6% (p < 0.001) and non-HDL cholesterol by 5.4 and 6.5% (p < 0.01). After 20 days of yerba mate intake, apolipoprotein B was reduced by 6.0% (p < 0.05) and HDL-cholesterol was increased by 4.4% (p < 0.01). In all participants triglyceride levels remained unchanged. The consumption of yerba mate by hypercholesterolemic individuals on statin therapy promoted additional 10.0 and 13.1% reductions in LDL-C after 20 and 40 days, respectively (p < 0.001) and increased HDL-cholesterol by 6.2% after 40 days (p < 0.05). It was thus concluded that intake of yerba mate infusion improved the lipid parameters in normolipidemic and dyslipidemic subjects and provided an additional LDL-cholesterol reduction in hypercholesterolemic subjects on statin treatment, which may reduce the risk for cardiovascular diseases.